2011
DOI: 10.1167/11.7.21
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to blur produced by ocular high-order aberrations

Abstract: The perceived focus of an image can be strongly biased by prior adaptation to a blurred or sharpened image. We examined whether these adaptation effects can occur for the natural patterns of retinal image blur produced by high-order aberrations (HOAs) in the optics of the eye. Focus judgments were measured for 4 subjects to estimate in a forced choice procedure (sharp/blurred) their neutral point after adaptation to different levels of blur produced by scaled increases or decreases in their HOAs. The optical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…Earlier studies showed HOAs blur adaptation to the blurred images produced after manipulation of natural HOAs with the source method (Sawides et al 2011a, Sawides et al 2011b, Sawides et al 2012). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies showed HOAs blur adaptation to the blurred images produced after manipulation of natural HOAs with the source method (Sawides et al 2011a, Sawides et al 2011b, Sawides et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The applications of psychophysical procedures have been seen in the studies on blur adaptation to astigmatism (Sawides et al 2010) and higher order aberrations (Sawides et al 2011a) in the literature.…”
Section: Psychophysical Methods To Measure Blur Adaptationmentioning
confidence: 99%
See 3 more Smart Citations